2017
DOI: 10.1038/nutd.2017.29
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Overweight and obesity in Mexican children and adolescents during the last 25 years

Abstract: Since the publication of the above article it has been noted that the author MC Morán-Ruán should have been listed as MC Morales-Ruán. The corrected article html and online pdf versions have been amended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…Moreover, results showed that per-capita intake of total and manufactured SSBs over the 1999 −2012 period increased sharply among low-SES children, while remaining the same among high-SES children. These observed trends in SSBs intake were mirrored with more pronounced increases in overweight and obesity among children from the lowest SES level (12) . The above-mentioned trends observed in school-aged children are a clear example of the nutrition transition experienced in Mexico; where a shift from traditional diets based on legumes, coarse grains and vegetables to processed, high in fat and sugar foods has occurred.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, results showed that per-capita intake of total and manufactured SSBs over the 1999 −2012 period increased sharply among low-SES children, while remaining the same among high-SES children. These observed trends in SSBs intake were mirrored with more pronounced increases in overweight and obesity among children from the lowest SES level (12) . The above-mentioned trends observed in school-aged children are a clear example of the nutrition transition experienced in Mexico; where a shift from traditional diets based on legumes, coarse grains and vegetables to processed, high in fat and sugar foods has occurred.…”
Section: Discussionmentioning
confidence: 91%
“…Mexico has one of the highest prevalences of excess body weight in the world, with 34.4% of school-aged children, 34.9% of adolescents and 71.3% of adults presenting overweight or obesity (11, 12) . Excess body weight has increased significantly during the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Al analizar los resultados por sexo, se puede apreciar que el 24,8% de las mujeres tiene sobrepeso y el 12,8% tiene obesidad, porcentajes similares al estudio de Hernández-Cordero y Cols. 30 , con 23,7% y 12,1% respectivamente. Lo mismo sucede con los porcentajes correspondientes a los hombres, quienes presentan un 16,7% sobrepeso y 12,5% de obesidad respecto al citado estudio con 19,6% y 14,5%.…”
Section: Resultsunclassified
“…Mexico is one of the countries with one of the most higher prevalence of obesity in children. (38) Recent evidence shows that in some extent obesity start on the first year of life.…”
Section: Discussion and Recommendationmentioning
confidence: 99%